2007
DOI: 10.1517/14656566.8.11.1743
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod: an immune response modifier in the treatment of precancerous skin lesions and skin cancer

Abstract: Actinic keratosis (AK) and basal cell carcinoma (BCC) are precancerous and cancerous skin lesions that should be treated especially when multiple or in cosmetically important areas. Apart from 5% 5-fluorouracil topical cream, which some feel is the gold standard topical treatment for AK, several invasive treatment modalities are available for AK and superficial BCC, such as cryotherapy, electrodessication, carbon dioxide laser and surgery causing patients discomfort and pain, pigmentary changes or necessitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(86 citation statements)
references
References 82 publications
0
86
0
Order By: Relevance
“…S2). A derivative of IMQ lacking TLR7/8 activity has been shown to stimulate cytokine production [26]. IMQ also triggers aerobic glycolysis, HIF-1a expression and IP3 receptor-dependent Ca 2+ signaling independently of TLR7/8 expression [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…S2). A derivative of IMQ lacking TLR7/8 activity has been shown to stimulate cytokine production [26]. IMQ also triggers aerobic glycolysis, HIF-1a expression and IP3 receptor-dependent Ca 2+ signaling independently of TLR7/8 expression [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly attributed to its induction of IFN‐ α in both animal models and humans . In addition, imiquimod was used as an antitumor agent in multiple mouse tumor models, with IFN‐ α being largely responsible for its effects . In fact, studies done in human peripheral blood mononuclear cell cultures showed that imiquimod induced the production of a vast pool of cytokines including IFN‐ α , TNF‐ α , IL‐1, IL‐1RA, IL‐6, IL‐8, IL‐10, IL‐12 p40, granulocyte colony stimulating factor, granulocyte/macrophage colony stimulating factor, macrophage inflammatory protein, and macrophage chemotactic protein‐1 .…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The 13-amino-acid peptide α-MSH (referred to as α-MSH 1-13 ) acts on the postsynaptic melanocortin 4 receptor (MC4R) in many brain regions to suppress appetite and stimulate metabolism (Figure 1). Failure of α-MSH 1-13 signaling due to mutations in the MC4R gene represents the most common form of genetically inherited human obesity (4).…”
mentioning
confidence: 99%
“…Whereas the events that lead up to activation of MC4R by α-MSH 1-13 are well known, virtually nothing is known about how α-MSH 1-13 activity is terminated. The extent of MC4R activation, and hence the extent of appetite loss, will be determined by the rate of α-MSH [1][2][3][4][5][6][7][8][9][10][11][12][13] release from POMC neurons and the rate at which it is degraded or otherwise cleared from the synaptic space. A seminal paper …”
mentioning
confidence: 99%